2019
DOI: 10.1016/j.ymssp.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic waves for materials evaluation in fatigue, thermal and corrosion damage: A review

Abstract: Mechanical properties of materials tend to deteriorate over time and thus become responsible for cracks and malfunctions in mechanical components or civil structures. Nondestructive ultrasonic wave analysis has proven to be a successful investigation method for inspecting mechanical properties of materials. This review has highlighted the main results of research in the field of non-linear ultrasonic wave investigations for the inspection of fatigue damage, thermal damage and chemical damage. In all three case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(55 citation statements)
references
References 113 publications
0
55
0
Order By: Relevance
“…Recent theories and related experimental studies have shown that the fatigue damage of metal materials in the early stage is related to the non-linear effect of ultrasonic waves [1][2][3][4][5]. In the early stage of fatigue damage to metals, the waveform is distorted when ultrasonic waves at a single frequency propagate therein due to the presence of various micro-defects such as dislocations, persistent slip bands (PSB), and micro-cracks, thus generating second harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theories and related experimental studies have shown that the fatigue damage of metal materials in the early stage is related to the non-linear effect of ultrasonic waves [1][2][3][4][5]. In the early stage of fatigue damage to metals, the waveform is distorted when ultrasonic waves at a single frequency propagate therein due to the presence of various micro-defects such as dislocations, persistent slip bands (PSB), and micro-cracks, thus generating second harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous degradation leads to predictable and unpredictable problems, sometimes with serious consequences. Therefore, it is necessary to do health testing for structures or materials in practical engineering [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Another important recent development exploits the much greater sensitivity of TOECs as compared with second-order elastic constants to dislocation driven damage (fatigue, creep, etc) [21][22][23]. This effect motivated the development of experimental techniques, such as second and higher harmonic generation to evaluate the so-called early damage [24][25][26][27], i.e. damage accumulated prior to the formation of a propagating crack.…”
Section: Introductionmentioning
confidence: 99%